PHILOSOPHY AND PHILOSOPHY OF ART FOR THE LEVEL OF IJCENCE - (:unkn) unknown (My University, 2014)
Bu çalışmanın amacı, sanat eğitimi veren fakülte/erde felsefe ve sanat felsefesi alan/arının önemini belirtmektir. Bunun yanında felsefe ve sanat felsefesi alanlarının nasıl etkili bir biçimde değer/endiri/eceğl üzerinde durulmuştur. Felsefe ve sanat felsefesi alanları eğitim fakültelerinin güzel sanatlar eğitimi bölümü programlarında koordineli bir şekilde yer almalıdır.

The purpose of this study, emphasizing the importence of philosophy and philosophy of art fields in the faculties of art education. Besides, focusing on philosophy and philosophy of art in the fields to assess how effectively. Fields of philosophy and philosophy of art, fine arts department of the faculty of education programs should take place in a coordinated manner.
Fakülte Ölçekli Eğitimde Felsefe ve Sanat Felsefesi
Keywords: Arkeoloji